2011
DOI: 10.1017/s0144686x11000195
|View full text |Cite
|
Sign up to set email alerts
|

Seeking respite: issues around the use of day respite care for the carers of people with dementia

Abstract: Ageing in Place policies have transferred responsibility for many frail elderly people and those living with dementia from residential to in-home care. Despite this placing a greater obligation on families, in Australia carers continue to under-use day respite services. This qualitative design study identified issues around the use of day respite care from the perspective of the family carer, focusing on barriers to attendance and strategies to facilitate attendance. Telephone interviews were held in 2007 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…In general, participants were grateful for the support they received; however, they recognised serious downfalls in institutional supports. Carers in this study identified reasons why they did not use services, and low utilisation was due, in part, to services not meeting their expectations for quality, relationship‐based care, a finding consistent with previous studies . Participants were more likely to use services when services were positive, and family, friends and health professionals provided the right information at the right time …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In general, participants were grateful for the support they received; however, they recognised serious downfalls in institutional supports. Carers in this study identified reasons why they did not use services, and low utilisation was due, in part, to services not meeting their expectations for quality, relationship‐based care, a finding consistent with previous studies . Participants were more likely to use services when services were positive, and family, friends and health professionals provided the right information at the right time …”
Section: Discussionsupporting
confidence: 84%
“…Views of people with dementia are commonly not included in research; however, inclusion of people with dementia in qualitative research is important in developing personalised and responsive services . Research concerning dementia and services in the Australian context has focussed on experiences of carers who use services and reasons for service use (or non‐use) but has not explored how the needs of carers and the people with dementia change as dementia progresses . A broader discussion of needs experienced by people with dementia and their carers, respectively, is required to develop services and systems that will benefit those living in the community .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, receiving day care services for their partners with dementia meant that informal caregivers could experience the feeling of being free to do whatever they wanted to do for some hours and enjoy having a breathing space. Experiencing being free and have some relief from the caregiver burden is crucial for the informal caregivers' opportunities to have a lifestyle with leisure or time for themselves [30]. Phillipson and Jones (2012) found that informal caregivers who use day care services tend to have accepted their own needs for breaks as legitimate [31].…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 99%
“…In the United States, United Kingdom and Australia, research has identified the challenges of providing effective respite care, not least in terms of encouraging uptake and ongoing engagement with services (e.g. Greenwood et al 2012, Robinson et al 2012, Phillipson et al 2013, McPherson et al 2014, Neville et al 2014). Shaw et al's (2009) systematic review identified three recurrent themes: carers had limited knowledge about availability of respite services, reported feeling frustrated by the processes of being assessed for services and could not access services which met their expectations.…”
Section: Introductionmentioning
confidence: 99%